2021
DOI: 10.3389/fcell.2021.748253
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbes and Hepatic Encephalopathy: From the Old Concepts to New Perspectives

Abstract: Hepatic encephalopathy (HE) is a severe complication of advanced liver disease and acute liver failure. The clinical spectrum ranges from minor cognitive dysfunctions to lethargy, depressed consciousness, and coma and significantly impact the quality of life, morbidity, and mortality of the patients. It is commonly accepted that the gut milieu is essential for the development of HE; however, despite intensive research efforts, the pathogenesis of HE is still not fully elucidated. As our knowledge of gut microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Over the last decade, increasing researchers pay more attention to the gut-liver-brain axis. The gut-liver-brain axis refers to the bidirectional relationship between the gut and its microbiota, the liver, and the brain, resulting from integrating signals generated by dietary, genetic, and environmental factors ( Rocco et al, 2021 ). Growing evidences have emerged to consider the microbiota-gut-liver-brain axis as a comprehensive approach for better understanding diseases pathophysiology ( Fuenzalida et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, increasing researchers pay more attention to the gut-liver-brain axis. The gut-liver-brain axis refers to the bidirectional relationship between the gut and its microbiota, the liver, and the brain, resulting from integrating signals generated by dietary, genetic, and environmental factors ( Rocco et al, 2021 ). Growing evidences have emerged to consider the microbiota-gut-liver-brain axis as a comprehensive approach for better understanding diseases pathophysiology ( Fuenzalida et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the gut environment is altered in patients with HE, resulting in structural and functional dysbiosis of the gut microbiota, decrease numbers of beneficial short‐chain fatty acid (SCFA)‐producing bacteria and increase in the abundance of harmful toxin‐producing bacteria with damaging effects on the intestinal barrier. [ 36 ] Furthermore, due to liver dysfunction and increased intestinal permeability, HE patients are unable to effectively remove gut‐derived toxins (including ammonia and LPS) that penetrate and accumulate in the bloodstream produced by the gut microbiota, which are key factors in inducing the systemic inflammatory response and high blood ammonia in HE. [ 13 ] Increasing researches have suggested that the brain‐gut axis takes on a critical significance in the connection and communication between the brain and the gut, and that both can undergo bidirectional signaling and regulation through neural, endocrine, and Immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of beneficial autologous taxa leads to decreased production of short-chain fatty acids (SCFAs), resulting in the conversion of primary bile acids into secondary bile acids, which further exacerbates gut dysbiosis, weakens the integrity of the intestinal barrier, reduces gut motility, and promotes small intestinal bacterial overgrowth (SIBO; Rocco et al, 2021 ). These changes amplify the rate of bacterial translocation and promote endotoxemia, introducing a significant amount of pathogen-associated molecular patterns (PAMPs) into the MLNs.…”
Section: Microbiota In Leptospirosis: Implications For Susceptibility...mentioning
confidence: 99%